INDUKSI KALUS TANAMAN KAKAO (Theobroma cacao L.) KLON SULAWESI 1 (S1) PADA MEDIUM MS DENGAN KOMBINASI HORMON 2,4-D, BAP DAN AIR KELAPA - Wilma Wilma; Muslimin Muslimin; I Nengah Suwastika (Biology Department, Mathematics and natural science, Tadulako University, 2014)
Kakao's seed that can result same plant better with it superior parent indispensable. One of alternative is with utilize vegetative organ origin seed that resulting through network culture tech by processes embriogenesis somatik. This research constitute startup phase in embriogenesis which is plant callus induction kakao. Research was performed on month of March until August 2013 at Network culture Laboratory, kehutanan's faculty. Tadulako's university. Eksplan who is utilized as staminodia of kakao's flower part Sulawesi clone 1. attempt it is arranged bases fledged Random Design (RAL) with 4 conducts and 3 time replicate. Each one unit experimentaling to utilize 10 eksplan. Conduct that dicobakan which is MS0 + 1ppm 2,4 - D. + 0,1ppm BAP + Coconut Water 15% (KW 1 ), MS0 + 1 ppm 2,4 - D. + 0,2ppm BAP + Coconut Water 15% (KW 2 ), MS0 + 2 ppm 2,4 - D. + 0,1ppm BAP + Coconut Water 15% (KW 3 ) and MS0'S medium + 2 ppm 2,4 - D. + 0,2ppm BAP + Coconut Water 15% (KW 4 ). Observed parameter is while its appearance callus, eksplan's percentage that results callus, and callus morphology. Preserve is done at dark place on temperature 26 ºC. Result observationaling to point out all conduct that dicobakan that menginduksi can kakao's callus. MS0'S medium + 2 ppm 2,4 - D. + 0,1ppm BAP + Coconut Water 15% (KW 3 ) constituting best media for menginduksi callus that marked by its appearance chromatic callus turns white, get intermediet's type, greater relative callus mass, uniform and active clefts to begin 14 days culture afterses. Keywords: MS, 2,4 - D., BAP, Coconut water, Callus induction, Staminodia, Theobroma cacao L.